Impaired autonomic function after incomplete revascularisation - Richard Armstrong; Rose Anne Kenny; Peter Wheen; Andrew Maree; Lisa Brandon; Ciarán Finucane (Open Heart, 2021)
Introduction Incomplete cardiac revascularisation (ICR) assessed by residual SYNTAX score (rSs) is associated with increased 5-year mortality. Furthermore, in the general population, our group has demonstrated that impaired autonomic function determined by heart rate recovery time between 10 and 20 s (HRR10–20) following an active stand is associated with increased all-cause mortality.Purpose We hypothesised that ICR would be associated with impaired autonomic function determined by HRR10–20.Methods After ethical approval and informed consent, consecutive patients attending cardiac rehabilitation in a tertiary referral centre were enrolled. All patients had percutaneous coronary revascularisation. During an active stand, real-time heart rate, blood pressure and ECG recordings were taken using non-invasive digital photoplethysmography and HRR10–20 determined. Assessment of autonomic function was performed by determining speed of HRR10–20 post-orthostatic challenge.Patients with an rSs >0 were considered incompletely revascularised and those with an rSs of 0 fully revascularised. Demographic data were recorded and statistical analysis performed.Results Patients (n=53) comprised those with complete revascularisation (CR) (n=37) and ICR (n=16). In the ICR group, mean rSs was 9.4.HRR10–20 was impaired in the ICR group (−3±0.60) compared with the CR cohort (−6.56±0.52) (p<0.0001). Completeness of revascularisation was strongly associated with HRR10–20 (Pearson’s correlation coefficient 0.529; p<0.0001). Baseline demographics did not differ significantly. Use of rate-limiting medication was similar between cohorts (beta blockers, calcium channel blockers, ivabradine).Conclusions Our data confirm significant correlation between ICR and impaired autonomic function determined by speed of heart rate recovery. Thus, determining autonomic dysfunction post-ICR may identify those at increased mortality risk.